1984
DOI: 10.1055/s-2007-1014690
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plasma Calcium Concentration on the Metabolic Clearance Rate of Calcitonin in the Dog

Abstract: Plasma immunoreactive calcitonin (iCT) levels generally are not elevated in chronic, nonmalignant, hypercalcemic states. Normocalcitoninemia might occur despite increased CT secretion if hypercalcemia itself accelerated the clearance of CT from the circulation. Therefore, we have measured the metabolic clearance rate (MCR) of human CT (hCT), infused to constant plasma levels in thyroparathyroidectomized dogs, under conditions of acute and chronic hypo- and hypercalcemia. Acute increases of plasma calcium were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…The peripheral metabolism of PTH is rapid; intact PTH is cleared from the circulation with a half-time disappearance of 2-5 min [5,6] . The majority of PTH (60-70%) is cleared from the blood hepatically, with the remainder (20-30%) cleared by the kidney [7,8] .…”
Section: Parathyroid Hormone: Synthesis and Bioutilizationmentioning
confidence: 99%
“…The peripheral metabolism of PTH is rapid; intact PTH is cleared from the circulation with a half-time disappearance of 2-5 min [5,6] . The majority of PTH (60-70%) is cleared from the blood hepatically, with the remainder (20-30%) cleared by the kidney [7,8] .…”
Section: Parathyroid Hormone: Synthesis and Bioutilizationmentioning
confidence: 99%
“…However, it seems unlikely that CT meta bolic clearance is affected in hypercalcemia. In fact, it has been demonstrated that during both chronic and acute hypercalcemia in ani mals [11], the metabolic clearance rate for human calcitonin is normal and of the same orde of magnitude as reported for normal human subjects [12].…”
Section: Discussionmentioning
confidence: 77%
“…p-Ca 2ϩ might affect the peripheral metabolism of PTH (33)(34)(35). It was observed by our group in the isolated perfused liver Figure 4.…”
Section: Discussionmentioning
confidence: 81%